Thermocline characteristics of molten-salt thermal energy storage in porous packed-bed tank. (5th January 2017) - Yin, Huibin; Ding, Jing; Jiang, Runhua; Yang, Xiaoxi
Highlights: Molten-salt heat storage in porous packed-bed tank is simulated. Local thermal equilibrium theory is applicable for thermocline heat storage. Stable thermocline layers form during the heat storage or heat release processes. Heat storage efficiency is affected by the thermocline and porous filler. The porous filler with larger volumetric heat capacity is favorable. Abstract: Based on the local thermal equilibrium theory in porous media, a two-dimensional numerical model is developed to investigate the heat storage and heat release processes of a molten-salt thermocline in a porous packed-bed tank. The numerical model is validated by comparing the simulation results with the experimental data. The performance of the heat storage system is analyzed using the thermocline thickness and the heat storage efficiency with a focus on energy balance. The results show that stable thermocline layers can form during heat storage or heat release processes. Because of the existence of the thermocline and replaced porous fillers, the heat storage efficiency in a porous packed-bed tank is slightly lower than that of pure molten-salt thermocline heat storage. The volumetric heat capacity of porous media is a key factor in heat storage performance. Improving the performance of the porous filler and setting the condition of a reasonably low flow rate, it can enable optimization control of the thermocline evolution in heat storage/release processes and improve the thermal efficiency of the heat storage system, which reveals directions for further research.